Deriving original nodule size of lithic reduction sets from cortical curvature: An application to monitor stone artifact transport from bipolar reduction. (February 2021) - Douglass, Matthew; Davies, Benjamin; Braun, David R.; Tyler Faith, J.; Power, Mitchell; Reeves, Jonathan
Highlights: A methodology for estimating the original size of stone nodules from remnant cortical curvature of flake and core products is presented. Computer simulation of experimental data demonstrates method's use with bipolar technologies. Approach expands interpretive perspective offered for bipolar assemblages. Abstract: Stone tools represent the largest source of information about past human behaviors on the planet. Much of the information about stone tools remains untranslated because we have little understanding about what the variation in artifact form means. One component of stone tool production that has less ambiguity is the reductive nature of the technology. Models of reduction rely on the ability to predict patterns of the rate of mass lost during artifact production. However, these patterns can vary quite substantially due to a variety of factors, one of which is variation in the original size of stone nodules prior to reduction. Here we report on a novel method to estimate the original size of stone nodules based on measurement of the curvature of residual cortex on flake and core products. Using experimental quartz bipolar reduction sets, we demonstrate the suitability of the approach, even when reduction intensity is high. Computer simulation with the experimental sets is then used to demonstrate the method's utility for supporting archaeological inferences about land use and mobility from the analysis of bipolar assemblages. The bipolar flaking method is a technique that was used widely across the 3 million years of paleolithic tool production, yet analytically has received less attention that other modes of reduction. Methods developed here will help to expand understanding for this analytically challenging technological context.